EFEKTIVITAS CANGKANG BUAH KENARI (Kanarium ovatum) SEBAGAI KARBON AKTIF DALAM MENGOLAH AIR LIMBAH INDUSTRI TEMPE UNTUK MENURUNKAN BOD, TSS DAN MENETRALKAN pH - Elvianto Zagoto; Charles Situmorang (FT-USNI, 2022)
This research was conducted to determine the characteristics of good activated carbon from the shell of a walnut (Kanarium ovatum). The purpose of this study was to treat tempe industrial wastewater using activated carbon from walnut shells (canarium ovatum). Tempe industrial wastewater treatment discharge 60 minutes and a dose of 14.4mg PH measurement results after processing from acid to neutral as well as in the BOD and TSS testing after processing using activated carbon with a dose of 14.4mg with a discharge of 30 minutes the test results decreased. The results showed that activated carbon from walnut shells (canarium ovatum) can be used in treating tempeh industrial wastewater. Activated carbon from walnut shells (canarium ovatum) can be used to treat tempe industrial wastewater.